2014
DOI: 10.1590/1809-2950/47321022014
|View full text |Cite
|
Sign up to set email alerts
|

Handgrip and functional mobility in elderly with different levels of physical activity

Abstract: | The proportion of elderly people is growing worldwide and, with this, there is an increase of chronicdegenerative conditions such as impaired balance and falls. The physically active elderly tends to an improved response in muscle strength, flexibility and postural balance. The present study aimed to evaluate and compare the grip strength and mobility of elderly people with different levels of physical activity. The sample consisted of 44 elderly with 60 years or more, both sexes, divided in: 18 elderly prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 21 publications
1
5
2
1
Order By: Relevance
“…Our findings agreed with earlier studies that reported an independent association between low HGS and functional mobility [ 43 , 44 ]. Notably, TUG performance was lowest among participants with low HGS, regardless of HGS symmetry, suggesting that low HGS and not asymmetry, was associated with functional mobility.…”
Section: Discussionsupporting
confidence: 94%
“…Our findings agreed with earlier studies that reported an independent association between low HGS and functional mobility [ 43 , 44 ]. Notably, TUG performance was lowest among participants with low HGS, regardless of HGS symmetry, suggesting that low HGS and not asymmetry, was associated with functional mobility.…”
Section: Discussionsupporting
confidence: 94%
“…There is a tendency for the decrease of FPM with the advancement of the age being that the decrease of the force of grip occurs of form more accelerated than the force of lower limbs. 19 It is reported that, in some studies, what is found is that women have the fragility component, for the grip strength variable, differently from what was found in this study, where the men were the ones with the greatest fragility.…”
Section: Resultscontrasting
confidence: 76%
“…A study with the elderly illustrated the difference between the hand grip strength means of elderly persons who fell and those who did not fall after institutionalization. A large part of the elderly persons residing in the community who had fallen had a lower HST score (11 to 20 kgf) than those who had not fallen (21 to 30 kgf) 23 .…”
Section: Discussionmentioning
confidence: 93%